Navigating an atypical presentation of peripheral stent infection: A case report of successful surgical salvage - Mouhammad Halabi, MD; Hassan Chamseddine, MD; Hamzah Saleem, MD; Jonathon Gould, MD; Loay Kabbani, MD; Mitchell Weaver, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Endovascular stent infections are a rare but potentially devastating complication that often present with nonspecific generalized signs and symptoms, leading to delayed diagnosis. We describe the case of a 46-year-old woman who developed progressive weakness and a diffuse rash of the left lower extremity 1 week after a left external iliac artery bare metal stent was placed for lifestyle-limiting claudication. Blood cultures were positive, and computed tomography angiography revealed fluid collection around the stent suggestive of infection. Despite targeted antibiotic therapy, her symptoms persisted, necessitating surgical stent explantation and arterial reconstruction with a cryograft. Postoperatively, she achieved full resolution of symptoms. This case underscores the diagnostic and therapeutic challenges of endovascular stent infections and highlights the importance of early recognition and intervention.